METODE TANYA JAWAB DALAM MENGEMBANGKAN KEMAMPUAN BAHASA ANAK - Mira Juliani; Dewi Ferawati (Institut Agama Islam Sultan Muhammaad Syafiuddin Sambas, 2021)
This study uses a qualitative approach and the type of descriptive research. Teacher planning in developing a question and answer method to develop language skills skills in children aged 5-6 years at TKIT Ya Bunayya Sambas by using prop by asking questions by means of the child’s imagination, then adjusting the emotions and development of children by inviting them to communicate directly,guiding by means of positive, and by singing and communicating in the right language.